The Poetic Edda A Dual-Language Edition - Pettit, Edward (Open Book Publishers, 2023)
This book is an edition and translation of one of the most important and celebrated sources of Old Norse-Icelandic mythology and heroic legend, namely the medieval poems now known collectively as the Poetic Edda or Elder Edda. Included are thirty-six texts, which are mostly preserved in medieval manuscripts, especially the thirteenth-century Icelandic codex traditionally known as the Codex Regius of the Poetic Edda. The poems cover diverse subjects, including the creation, destruction and rebirth of the world, the dealings of gods such as Óðinn, Þórr and Loki with giants and each other, and the more intimate, personal tragedies of the hero Sigurðr, his wife Guðrún and the valkyrie Brynhildr. Each poem is provided with an introduction, synopsis and suggestions for further reading. The Old Norse texts are furnished with a textual apparatus recording the manuscript readings behind this edition's emendations, as well as select variant readings. The accompanying translations, informed by the latest scholarship, are concisely annotated to make them as accessible as possible. As the first open-access, single-volume parallel Old Norse edition and English translation of the Poetic Edda, this book will prove a valuable resource for students and scholars of Old Norse literature. It will also interest those researching other fields of medieval literature (especially Old English and Middle High German), and appeal to a wider general audience drawn to the myths and legends of the Viking Age and subsequent centuries.